1963
DOI: 10.1113/jphysiol.1963.sp007264
|View full text |Cite
|
Sign up to set email alerts
|

The effect of heating the hypothalamus and the skin on the rate of moisture vaporization from the skin of the ox (Bos taurus)

Abstract: Localized heating of the hypothalamus of the ox causes an increase in the rate of moisture vaporization from the skin of the trunk when the environmental temperature is between 10 and 200 C (Ingram, McLean & Whittow, 1961). The increased moisture loss from the skin is associated with an increase in the skin temperature. It is uncertain whether the increase in cutaneous moisture loss is a direct effect of increased hypothalamic temperature or whether it is a secondary effect of increased skin temperature. Nor i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1966
1966
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…Such stimuli are effective in the control of sweating in man, during transient thermal states (Wurster, McCook & Randall, 1966). This might be true in cattle also only in the transient conditions of the natural climate, as hypothalamic heating was found to activate sweating (Ingram, McLean & Whittow, 1963).…”
Section: Discussionmentioning
confidence: 99%
“…Such stimuli are effective in the control of sweating in man, during transient thermal states (Wurster, McCook & Randall, 1966). This might be true in cattle also only in the transient conditions of the natural climate, as hypothalamic heating was found to activate sweating (Ingram, McLean & Whittow, 1963).…”
Section: Discussionmentioning
confidence: 99%
“…Further evidence of vascular involvement in sudomotor action comes from the experiments of Ingram et al ., 109 who showed that in the ox, sweating caused by localized heating of the hypothalamus did not occur when the circulation was occluded. An interaction between sweating and the microcirculation is also readily evident from experiments on isolated perfused equine skin 49,71 .…”
Section: Control Of Sweatingmentioning
confidence: 99%
“…Additionally, there are relationships between atopic, wrinkled skin and other skin diseases with TEWL. Therefore, research into moisturizing and prevention of moisture loss is needed to enhance the elasticity and smoothness of skin (Thiex and Richardson, 2003;Rawlings and Matts, 2005;Ingram et al, 1963;Sarkar et al, 2010).…”
Section: Introductionmentioning
confidence: 99%